PEMANFAATAN APLIKASI OWNCLOUD PADA SISTEM KEAMANAN CLOUD COMPUTING - Edy Rakhmat; Saleh Dwiyatno; Sulistiyon Sulistiyon; Agus Irawan; Ferli Setiawan (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
Private cloud is a type of private storage or only provides limited services to an organization or an agency. OwnCloud is a company whose project is OwnCloud project. The company's slogan is "Your Cloud, Your Data, Your Way". OwnCloud is one of the free file sharing software and has provided free security and has an easy or user-friendly user interface so it is easy to use. Owncloud has several features such as creating groups, being able to easily control users and having several other features that are a solution for a cloud-based storage at the Banten Province Public Works and Spatial Planning Office UPTD Serang – Cilegon roads and bridges which do not have integrated storage and still rely on storage such as hard drives, Google Cloud and available storage on the computer or PC in the office which makes it easy to lose and not integrated, therefore a solution using owncoud is made to reduce the existing storage on the computer or PC in the office This is so that all files are stored neatly and by adding a security so that every existing user cannot access data on other users, thus the data can be maintained and cannot be seen by other irresponsible people so that it is easier to operate. its n. By using ownloud which has several features, it makes owncloud more practical.